1996
DOI: 10.1093/carcin/17.12.2763
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of DNA adducts by cisplatin, lobaplatin and oxaliplatin in calf thymus DNA in solution and in cultured human cells

Abstract: Two interesting representatives of a new generation of platinum-based cytostatic drugs that are currently being tested in clinical trials are lobaplatin [1,2-diaminomethylcyclobutane platinum(II) lactate] and oxaliplatin [1,2-diaminocyclohexane platinum (II) oxalate]. Since little is known about the DNA adduct formation of these compounds, we studied their formation in DNA in vitro in calf thymus DNA and in cells. The major adducts formed in vitro were the Pt-GG and Pt-AG intrastrand crosslinks. The latter add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
78
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 21 publications
10
78
0
4
Order By: Relevance
“…DDP has been effective in inducing apoptosis in variety of tumor cell lines (40 -42). Its apoptosis-inducing effects are known to be correlated with DNA damage by forming DNA-Pt adducts and DNA strand breaks (40,41). Recently, evidence indicated that CXCL10 reduced microvessel density, leading to the observed increase in both tumor cell apoptosis and necrosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…DDP has been effective in inducing apoptosis in variety of tumor cell lines (40 -42). Its apoptosis-inducing effects are known to be correlated with DNA damage by forming DNA-Pt adducts and DNA strand breaks (40,41). Recently, evidence indicated that CXCL10 reduced microvessel density, leading to the observed increase in both tumor cell apoptosis and necrosis (43).…”
Section: Discussionmentioning
confidence: 99%
“…As with cisplatin-DNA damage, the 1,2-intrastrand d(GpG) and d(ApG) cross-links formed by these closely related platinum compounds most likely contribute to their cytotoxicity. For example, oxaliplatin forms mainly 1,2-intrastand d(GpG) cross-links both in vitro and in cells (14,15). Therefore, understanding how these spectator ligands, ammonia in the case of cisplatin and 1,2-diaminocyclohexane in the case of oxaliplatin, affect the binding of cellular proteins to platinated DNA may help to distinguish the manner by which the proc-essing of their lesions in the cell can differ from that of cisplatin-damaged DNA.…”
Section: Cis-ddp Cis-diamminedichloroplatinum(ii) (Cisplatin)mentioning
confidence: 99%
“…Following reaction with DNA, the adducts differ by virtue of the fact that the cisplatin adduct has two amino groups projecting into the major groove whereas the oxaliplatin adduct retains the bulkier DACH ring. The major adducts formed by oxaliplatin are the Pt-GG and Pt-AG intrastrand cross-links (Saris et al, 1996). Sedimentation analysis showed that oxaliplatin does not induce detectable interstand cross-links but forms DNA strand breaks (Woynarowski et al, 1997).…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…In contrast, cisplatin produces interstand crosslinks but no breaks. Oxaliplatin appears to be less reactive with cellular DNA than cisplatin, but is a comparably potent inhibitor of DNA and protein synthesis (Saris et al, 1996;Woynarowski et al, 1997).…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%